DETERMINATION OF ADULT PATIENT SKIN ENTRANCE AND EFFECTIVE DOSES FOR SOME SELECTED X-RAY DIAGNOSTIC EXAMINATION IN NIGER STATE - Muhammad, Abdullahi; Lazarus, J. A.; Ibrahim, A. A.; Shehu, M. S. (FUDMA JOURNAL OF SCIENCES, 2025)
The ionizing radiation exposure to patients receiving standard X-ray examinations was evaluated in this paper. To make sure the patient’s X-ray dose was within an acceptable range, the skin entrance dose (SED) and effective dose (ED), which determine the amount of absorbed radiation dose to the body, were measured. The mean SED and ED results were then compared with the international standard threshold values. Caldose_x 5.0 software was employed to examine the Skin Entrance Dose (SED) and effective dose (ED) of seven types of routine X-ray examinations in three public hospitals in Niger State, Nigeria. The routine examinations are: cervical spine (AP/LAT), thoracic spine (AP), pelvis (AP), thorax (PA/LAT) and lumber spine (AP). For each projection, the X-ray tube supplied a constant potential (no ripple), with X-ray emission angle of 17o and a total filtration of 2.5 mm aluminum (Al). 229 patients diagnostic X-ray were examined with approximately 52 % male and 48 % female. In other to calculate patients’ SED and ED using Caldose_x, patients’ data such as age, sex, projection, type of examination, mAs and kVp were inputed. The output mean SED and ED were compared with internationally established diagnostic reference levels and published results. The estimated mean SED were 0.23, 1.99, 1.09, 0.38, 3.95, 0.24, 0.41 mGy and the mean ED were 0.05, 0.65, 0.06, 0.02, 0.35, 0.05, 0.03 mSv, for the seven examination projection. The Caldose_x software analysis of routine X-ray examinations revealed that the SED and ED values were largely in agreement with international standards.